Socio-economic impacts on local community in Pangkor Island - Ismail, Safura; Mohd Bakri, Norjanah; Jaafar, Mastura (2013)
Since 1990s, the impact of tourism development has grown tremendously especially in the spectra of islands and marine parks tourism. Despite the fact that most of the Malaysian islands already have their individual ecotourism natural attractions, more islands have been progressively developed as a tourist attractions spot. The scenario has given an economic advantage to the local community where many society members have shifted their profession from fishing to ecotourism-related activities. However, inappropriate tourism development and growth can lead to adverse environmental and socio-economic impacts on the islands, including exposing the local community to certain foreign behaviours that may opposed to the island culture or traditional community values. Pangkor Island is one of the renowned islands in Malaysia, located in the Perak state and just off the coast of North West Malaysia. Another name for Pangkor Island long ago was Dinding, which means 'screen' or 'partition'. There are five main attractions of Pangkor Island that are coastal areas, island resorts, historical sites, forest areas and cultural activities. Based on Life Cycle Theory, Pangkor Island is currently facing declination stage where it used to experience booming tourism period in the past 20 years. The impact of previous development on the local community socio-economic provides a significant research area to be explored. Interviews have been conducted with several notable people in Pasir Bogak and Teluk Nipah to assess the socio-economic impact on the local community in Pangkor Island.